An Evolutionary Strategy for Identification of Higher Order, Green Fluorescent Host–Guest Pairs Compatible with Living Systems. Issue 70 (9th November 2020) - Casey, Garrett R.; Zhou, Xinqi; Lesiak, Lauren; Xu, Bi; Fang, Yuan; Becker, Donald F.; Stains, Cliff I.
Abstract: Engineered miniprotein host–small‐molecule guest pairs could be utilized to design new processes within cells as well as investigate fundamental aspects of cell signaling mechanisms. However, the development of host–guest pairs capable of functioning in living systems has proven challenging. Moreover, few examples of host–guest pairs with stoichiometries other than 2:1 exist, significantly hindering the ability to study the influence of oligomerization state on signaling fidelity. Herein, we present an approach to identify host–guest systems for relatively small green fluorescent guests by incorporation into cyclic peptides. The optimal host–guest pair produced a 10‐fold increase in green fluorescence signal upon binding. Biophysical characterization clearly demonstrated higher order supramolecular assembly, which could be visualized on the surface of living yeast cells using a turn‐on fluorescence readout. This work further defines evolutionary design principles to afford host–guest pairs with stoichiometries other than 2:1 and enables the identification of spectrally orthogonal host–guest pairs. Abstract : Evolution of higher order supramolecular assembly in a miniprotein host–green fluorescent guest system compatible with living cells.